(untitled) (International Journal of Environmental Sciences, 2025)
Robot anthropomorphism and precision are improved by teleoperation technology. In order to improve overall control and effectiveness, perception technology—especially multimodal sensor systems with tactile feedback—is essential for giving operators a greater grasp of the robot’s condition and environment. It is used more often in medical rehabilitation, such as when prosthetic hand sensors trigger nerves to produce natural touch. Robot finger pads with tactile sensors can sense pressure from the outside, facilitating accurate engagement. Anthropomorphism is still difficult to achieve, though, especially when it comes to recognizing human motion and incorporating it into the robot’s decision-making process, which is essential for smooth control and human-like functionality. The complex biomechanical structure of the human arm, which includes flexible joints and multiple degrees of freedom, enables people to perform a variety of challenging tasks. In order to achieve anthropomorphic control and replicate human-like movements, precise kinematic mapping is crucial because robotic arms frequently have rigid constructions and few degrees of freedom. Its solution plays a key role in increasing the versatility of robotic arms in many applications.